2008
DOI: 10.1016/j.revmic.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental change on early Aptian ostracods faunas in the Wessex Basin, southern England

Abstract: A major phase of transgression in the Wessex Basin (southern England) during the earliest Aptian resulted in the collapse of the generally fresh water Barremian environment and the initiation of the marine mileu.Cypridea-rich faunas low in the Shepherd's Chine Member (Vectis Formation), were gradually replaced by faunas dominated by Sternbergella cornigera, Mantelliana mantelli and Theriosynoecum fittoni. This change is interpreted as indicating that salinities had passed from fresh-oligohaline to meso-and pli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In Atherfield, sampling was focused on the Atherfield Clay Formation (Table 1). Below is a succinct description of the studied lithostratigraphic units in the Isle of Wight based on previously published works (Casey, 1961;Owen, 1975;Batten, 1982;Batten, 1994, 1990;Ruffell and Wach, 1991, 1998b, 1998aStewart et al, 1991;Wach, 1991;Wach and Ruffell, 1991;Harding and Allen, 1995;Gröcke et al, 1999;Gröcke, 2002;Robinson and Hesselbo, 2004;Wilkinson, 2008;Hopson et al, 2008Hopson et al, , 2011.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…In Atherfield, sampling was focused on the Atherfield Clay Formation (Table 1). Below is a succinct description of the studied lithostratigraphic units in the Isle of Wight based on previously published works (Casey, 1961;Owen, 1975;Batten, 1982;Batten, 1994, 1990;Ruffell and Wach, 1991, 1998b, 1998aStewart et al, 1991;Wach, 1991;Wach and Ruffell, 1991;Harding and Allen, 1995;Gröcke et al, 1999;Gröcke, 2002;Robinson and Hesselbo, 2004;Wilkinson, 2008;Hopson et al, 2008Hopson et al, , 2011.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…S4, Table S3). The species composition of Lower Cretaceous ostracod assemblages of Crimea appears to be affected by a marked endemism and thus none of the proposed zonations (Neale 1978;Wilkinson & Morter 1981;Damotte et al 1981;Babinot et al 1985;Lott et al 1985Lott et al , 1986Wilkinson 1988Wilkinson , 2008Vivers et al 2000;Woods et al 2001;Coimbra et al 2002;Bachmann et al 2003) can be applied in this area. Nevertheless, the recent study of ostracod stratigraphic distribution in the upper Barremian-Aptian sediments of the SW Crimea enabled the recognition of several correlative ostracod Zones (Karpuk 2016 b;Brovina et al 2017), which were also found in the Zavodskaya Balka section.…”
Section: Ostracodamentioning
confidence: 99%